2021
DOI: 10.2147/phmt.s323526
|View full text |Cite
|
Sign up to set email alerts
|

Survival Status and Predictors of Mortality Among Low-Birth-Weight Neonates Admitted to the Neonatal Intensive Care Unit at Felege Hiwot Comprehensive Specialized Hospital, Bahir Dar, Ethiopia, 2020

Abstract: Background: Low birth weight neonates are subjected to different comorbidities due to anatomical and physiological immaturity. Globally, 60-80% of neonatal mortality was due to low birth weight. Hence, this study aimed to assess the survival status and predictors of mortality among low birth weight neonates. Methods: An institutional-based retrospective cohort study design was conducted among 718 low birth weight neonates admitted to the neonatal intensive care unit from January 1, 2017, to December 30, 2019, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 21 publications
2
12
1
Order By: Relevance
“…Neonates with small size at birth were more likely to die than neonates with large size at birth. This is consistent with studies [25,28,29]. Multiple births were more likely to die in the first month of birth than singletons.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Neonates with small size at birth were more likely to die than neonates with large size at birth. This is consistent with studies [25,28,29]. Multiple births were more likely to die in the first month of birth than singletons.…”
Section: Discussionsupporting
confidence: 91%
“…Neonates born at health facilities were less likely to die than neonates born at home. This is consistent with the studies [25,29,30]. This could be due to that mothers who give birth at health facilities may be given health information regarding the care of the child.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, like the previous study ( 33 ), low birth weight was also one of the determinant factors for NICU admission in our study. Other studies also indicated that low birth weight was associated with low Apgar scores and neonatal deaths ( 34 , 35 ). These findings revealed that prematurity and low birth weight are associated with adverse perinatal outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…Neonates having low birth weight are at a higher risk of facing death because of underdeveloped organs, life sustaining systems, and also because of their inability to physically react against the external environment in which they are placed. 12 Problems linked with LBW i.e. mortality in infants are of serious nature.…”
Section: Discussionmentioning
confidence: 99%